Rancang Bangun Tuneable Bandpass Filter Combline untuk VHF Air Ground Radio Communication - Muhammad Arif Sulaiman; Toni; Muh Wildan; Quwarazmi Golddin Al Farraz (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
Aviation radio communication services between Air Traffic Control and pilots must be maintained in good condition without interruption because flight safety is the main priority. The goal of the research is to reduce unwanted frequency harmonics generated from the transmitter so that the effect of frequency interference on adjacent channels can be reduced. This tool will only miss the expected frequency. This bandpass filter is set up carefully to be able used in the VHF Air Ground Communication frequency range, namely 118 – 137 MHz with a tunable combline model which has high selectivity in the frequency channel used. This research method is the design and analysis of a tool consisting of several cylindrical rod transmission lines (slabline) connected to ground at one end and a variable capacitor attached along with ground at the other end. The simulation results and measurements of insertion loss (S21) and return loss (S11) parameters still meet design standards in all VHF A/G frequency ranges. Equipment performance was tested with a working frequency of 120.0 MHz on VHF AG radio transmitter equipment Brand Icom A-120 with a power of 9 Watts, Brand Rohde & Swarch SU4200 with a power of 5 Watts, and Dittel FSG-2T with an output power of 3 Watts. Test results using the equipment can still be used with VSWR results still less than 2 and a decrease in power output of less than 20% of the nominal power.